Les paons affrontés dans l’art lombard des viii e‑ix e siècles - Raphaël Demès (Frontière·s)
In the ecclesial space, the chancel clearly separates the nave from the choir, marking a boundary between the clergy and the faithful. The image of the peacocks facing each other on several Lombard chancels between the 8th and 9th centuries offers us a precious source of reflection on the close links between the decoration and its support. In this position, the peacocks obstruct the passage of the faithful, thus embodying perpetual guardians of the threshold of the choir, gathered around the cross and/or the chalice on which they watch. By drinking from the chalice or by satiating themselves with the fruits of the Cross-Tree of Life, the peacocks are nourished with eternal life and bring hope of salvation to the faithful who draw closer to Christ through the Eucharist. Perceived as a psychopomp since antiquity, the peacock accompanies the spiritual elevation of the faithful and imposes itself as an additional mediator between the earthly and the heavenly. Gathered together at the threshold of the choir, the peacocks in confrontation relay the scope of the sacrament of communion and invite the faithful to cross the frontier of the material, the visible, the sensitive. The image of the peacocks faced on these chancels thus participates in the spiritualisation of the carnal and the appeasing of the tension between body and soul. The three chancels studied thus show the liminality of a visual support anchored in the ecclesial space at a point of tension between nave and choir, while highlighting the role of the image of the peacocks confronted as a visual relay of this limilality, both as guardians and as mediators.